Beyond the black mirror effect: the impact of machine translation in the audiovisual translation environment - de los Reyes Lozano, Julio; Mejías-Climent, Laura (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2023)
In an increasingly globalized world, technological advancements and artificial intelligence (AI) have catalysed the proliferation of audiovisual productions and their translation, leading to new dynamics in the professional landscape. Tools and practices such as machine translation (MT) and post-editing (PE) are becoming widespread, augmenting and diversifying translators’ tasks and creating new professional profiles and educational needs. While some specialized fields with more restrictive languages and terminology have readily incorporated MT, recent developments in neural MT (NMT) engines have led to their use in more creative areas such as literary or audiovisual translation (AVT). However, this trend raises concerns about the quality of both the raw and the final output, user perceptions, ethics and working conditions. Academic studies which explore the convergence of MT and AVT therefore become crucial to understanding the implications of this technology for all stakeholders: professionals, students and instructors, researchers, audiences and society at large. This article delves into the impact of neural MT and other AI-based tools on AVT workflows, both professionally and academically, and stresses the need for further research in this area. It then proceeds to outline the main research directions in this field as evidenced by the contributions included in this special issue, particularly those regarding the incorporation of MT into different AVT modes.